PROGRAM PEMBELAJARAN MADRASAH DINIYAH (MADIN) SEBAGAI SOLUSI UNTUK MENINGKATKAN PENGETAHUAN AGAMA BAGI SISWA SEKOLAH UMUM - Wardi, Suhra (Universitas Tanjungpura, 2019)
Human Resource Development is a key factor to achieve the progress of the country and nation. Creating quality human resources is not only in terms of intellectual intelligence, but more important is the religious intelligence. Religion teaches that there is damage on earth because of human actions. Achieving prosperity and peace for all mankind will be achieved and felt because of the balance of intellectual and religious intelligence, so that life peace is expected and avoid damage on earth. Pontianak City Government anticipates the realization of a balance of intellectual and religious intelligence throughthe establishment of the Madrasah Diniyah Takmiliyah program for public schoolstudents. The Pontianak City Government implements this program in collaboration with the Pontianak City Ministry of Religion and the Pontianak State Islamic Institute (IAIN). This policy was taken because of the lack of religious material for public school students in the national curriculum. Regional autonomy makes it possible for the Regional Head to stipulate Regional Regulations (Perda) related to strengthening religious education needed by the region in order to achieve the welfare of the community.